Proposta de gestão remota de resíduos da construção civil em edificações - Vendramim, Julia Maria Carmona (Universidade Federal de São Carlos, 2023)
The civil construction widely used in Brazil is still predominantly manual and artisanal and the level of industrialization is not as present when compared to other sectors, which already follow Industry 4.0. Updating civil construction management practices in relation to new technologies can be beneficial for gains in productivity and process efficiency. Thus, the remote management of civil construction waste (RCC) can also enjoy these benefits. In this context, the present work aims to develop a remote management model of RCC at the construction site with a focus on buildings. To this end, a bibliographical review was carried out on the principles and technologies of Industry 4.0 and, based on this information, a model for remote management of RCC was structured. As a result, the desired model was obtained, the technologies that can be used at each stage, the agents of each process, the correlation of processes with the principles of Industry 4.0 and flowcharts that can be used to develop a remote management tool based on the developed model. As conclusions of the work, it was understood that the remote management of RCC is dependent not only on the management model used, but also on the technologies employed, which are decisive for the “remote” to be really put into practice. It is understood, therefore, that the key point for the use of remote management of RCC is the use of technologies.
Proposal for remote disposal of construction waste in buildings
Keywords: Entulho; Gestão de resíduos; Gestão remota; Indústria 4.0; Modelo de gestão; Industry 4.0; Management model; Remote management; Rubble; Waste management; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL